Asuhan Keperawatan Jiwa pada Ny. R Dengan Masalah Utama Risiko Perilaku Kekerasan Akibat Skizofrenia Tak Terinci di Ruang Arimbi RSJD dr. Amino Gondohutomo Provinsi Jawa Tengah - Siska Alfiyatul Aulia; Titi Sri Suyanti; Slamet Wijaya Biantoro (Calory Journal Medical Laboratory Journal, 2025)
Schizophrenia is a syndrome with a variety of causes, where each patient exhibits different clinical manifestations, therapeutic responses, and disease progression. Clinical manifestations of schizophrenia include disorganized speech, restlessness, pacing, and aggression, often exhibited through violent behavior. According to WHO data, in 2019, approximately 24 million people worldwide suffered from schizophrenia (WHO, 2019). The purpose of this paper is to understand the nursing care process for Mrs. R, with the main issue being the risk of violent behavior due to unspecified schizophrenia. The writing method used is a descriptive case study through a nursing process approach, where the assessment is conducted using interview techniques, observation, documentation review, and literature study. The nursing diagnoses identified include the risk of violent behavior, self-concept disturbance: low self-esteem, and self-care deficit. The interventions developed involve implementing strategies for both the patient and the family. The evaluation of the nursing care for Mrs. R showed that the diagnosis of risk of violent behavior was partially resolved, and the self-care deficit was resolved.